CLINICAL AND MICROSURGICAL ANATOMY OF THE ILEOCECAL VALVE - O. B. Dronova; I. N. Fateev; A. M. Adegamova; D. V. Savin; A. N. Shepelev (Креативная хирургия и онкология, 2017)
The article reflects the need for extensive use in the application of fundamental anatomical studies ileocecal region results research methods, quantitative estimates of the morphological parameters, that are opening new possibilities for diagnosis of pathological processes and development of new ways of operating.